Graphene oxide and its viability as a constituent in nanofertilizers - Saraiva, Raquel; Ferreira, Quirina; Rodrigues, Gonçalo C.; Oliveira, Margarida (Frontiers in Nanotechnology, 2025)
The use of chemical fertilizers and phytochemicals is a common practice in major crop production, promoting increased production per hectare but also representing a growing environmental concern. In response to this problem, this work carried out an ecotoxicity study and characterized the changes in soil properties resulting from the use of graphene oxide (GO), a component used in the formulation of new nanofertilizer and nanobiostimulant pellets for agriculture due to its effective carrier properties and previously reported non-toxicity in other areas. Lepidium sativum L. petri dish and pot trials were performed according to the EN 16086-2 European Standard and OECD guidelines to evaluate germination, vitality, and root development. Soil parameters such as pH, electrical conductivity (EC), total organic carbon (TOC), and water holding capacity (WHC) were also monitored. Although no significant phytotoxic effects were observed at most concentrations, higher doses (2.00 mg mL−1) exhibited deviations in plant behavior and TOC levels. These findings help define the preliminary safe-use thresholds for GO in agricultural applications.